Penerapan Food Model dalam Asuhan Keperawatan Keluarga dengan Pemenuhan Nutrisi pada An.A di Desa Tongkaina Kecamatan Bunaken - Jordan Kevin Lampah; Simak, Valen Fridolin; Larira, Dina Mariana (Program Studi Ilmu Keperawatan Fakultas Kedokteran Universitas Sam Ratulangi, 2025)
Background. School children are experiencing growth and development and therefore need food intake that contains balanced nutrition, so that the process is not disturbed. The role of parents is very important in meeting the nutritional needs of children, but there are various factors that can hinder this ability, such as lack of food availability in the household, poor feeding methods, children do not want to eat or other social factors. Objective. This study aims to describe family nursing care with the developmental stages of school-age children. Method. This research is a type of descriptive research by taking secondary data from family members who are under their supervision. Results. Nursing problems that arise in managed families more specifically in An. A are nutritional imbalances less than the body's needs, delays in child development and health behaviors tend to be at risk. Keywords: nursing problems, nutritional needs, children.